Protective Effect of Zizyphus lotus L. (Desf.) Fruit against CCl(4)-Induced Acute Liver Injury in Rat - Bencheikh, Noureddine (Evid Based Complement Alternat Med, 2019)
In Morocco, “Zizyphus lotus L.” is one of the most widely and traditionally used plant species to treat various diseases, including liver disorders. The present study was conducted to evaluate the aqueous extract of Zizyphus lotus L. fruit against carbon tetrachloride- (CCL(4)-) induced liver damage in Wistar rats. The animals were daily treated with the aqueous extract of Zizyphus lotus L. fruit using two doses separately 200 and 400 mg/kg body weight for 14 days. CCL(4) was injected intraperitoneally (1 ml/kg body weight) at two times, 7(th) and 14(th) days. At the end of the treatment, rats were sacrificed, and the blood was collected for the assessment of biochemical parameters. Moreover, the body weight as well as liver weight was determined. The injection of CCl(4) to the rats induced various alterations such as the increase of relative liver weight, serum alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, total bilirubin, direct bilirubin, triglycerides, very low-density lipoproteins, total cholesterol (slight increase), creatinine, urea, uric acid, and malondialdehyde. On the contrary, the effects of CCL(4) lead to the reduction in serum levels of high-density lipoprotein. However, the daily administration of the aqueous extract of Zizyphus lotus L. fruit to the injected rats with CCL(4) restored this abnormal variation in these biochemical parameters to normal values. Based on the results obtained in this study, it seems that the aqueous extract of Zizyphus lotus L. fruit has an hepatoprotective effect against hepatic lesions induced by CCL(4) in rats.